MANUFACTURING FIRMS’ CAPITAL STRUCTURE IN BANGLADESH: COMPARISON BETWEEN LISTED MNCS AND LOCAL COMPANIES - Rahman, Syed Mohammad Khaled; Tania, Tasmina Chowdhury (International Journal of Accounting & Finance Review, 2021)
The capital structure of a firm has immense significance as it has implications on corporate value and financial performance. The basic aim of the research was to analyze and compare the capital structure of Dhaka Stock Exchange (DSE)-listed multi-national companies (MNCs) and local companies of Bangladesh over 24 years (1996-2019). Stratified sampling techniques were applied to the selection of firms. Six financial leverage ratios were used to analyze and compare capital structures. There were significant differences in capital structure between local companies and MNCs as the null hypothesis was rejected. It was also found that the mean equity-financing proportion of domestic companies and MNCs were 65% and 92.5% respectively. The proportion of long term debt in total capital employed was very low for both types of companies. MNCs can raise the proportion of both short and long-term debt to take the advantage of financial leverage. Domestic companies can redeem some short term loan and replace some short term debt with long term debt. This research would be useful for corporate financial managers, creditors, and investors to take appropriate financing as well as investment decisions which would affect shareholders' wealth and value of the firm in the long run to a significant extent.JEL Classification Codes: G30, G32, G39